Advocating for a Loved One in the Setting of Uncertainty: A Mixed-Methods Study Among Caregivers of Sepsis Survivors at the Point of a Sepsis Readmission. Issue 1 (January 2021) - Umberger, Reba A.; Todt, Kendrea; Talbott, Elizabeth; Sparks, Laurie; Thomas, Sandra P.
Abstract : Background: The trajectory of recovery after sepsis varies. Survivors may have considerable ongoing limitations, requiring a caregiver for a prolonged period. Objectives: To learn about experiences, quality of life, coping, resilience, and social support of caregiver caring for survivors of sepsis. Methods: We conducted a convergent mixed-methods study, recruiting informal caregivers of patients who had survived sepsis in the past year and were readmitted to the intensive care unit with sepsis. Individual face-to-face, semistructured interviews and validated surveys on quality of life, coping, caregiver burden, resilience, and social support were administered to caregivers. Interview transcripts were analyzed using content analysis. Surveys were scored and summarized using descriptive statistics. Results: Caregivers were primarily middle-aged, White, and female. Half were spouses of their care recipient. Caregivers reported some deficits in mobility, pain, and anxiety/depression. Coping styles varied, with engaged coping being more prevalent. Most caregivers reported mild to moderate burden, all reported either normal or high resilience levels, and types of social support were similar. However, interviews and survey findings were not always consistent. Major themes that emerged from the analysis included (1) advocating for and protecting their loved one, (2) coping with caregiving, (3) uncertain future, (4) rewards of caregiving, and (5) need to optimize communication with family. Discussion: Caregivers of sepsis survivors are protective of their care recipient and use a variety of strategies to advocate for their loved one and to cope with the uncertainty involved in a new intensive care unit admission. More advocacy and support are needed for this population.